Altered amplitude of low-frequency fluctuation and functional connectivity in patients with acute unilateral vestibulopathy: a resting-state fMRI study - Chen, Zhengwei; Rong, Liangqun; Xiao, Lijie; Rao, Jie; Liu, Haiyan; Liu, Tengfei; Chen, Fei; Zhang, Jun; Wang, Lu; Li, Xi; Wei, Xiue (Frontiers in Neurology, 2025)
ObjectiveTo investigate changes of brain functional activity in patients with acute unilateral vestibulopathy (AUVP) using functional magnetic resonance imaging (fMRI).MethodsWe studied 32 AUVP patients and 30 healthy controls (HC) who received resting-state fMRI scanning. Methods of voxel-based amplitude of low-frequency fluctuation (ALFF) and seed-based functional connectivity (FC) were adopted to compare the difference in brain function between the two groups. In addition, we evaluated the associations between abnormal neuroimaging results and clinical data in AUVP patients.ResultsCompared with HC, patients with AUVP showed lower ALFF in brain regions of bilateral insular, right precentral gyrus, left inferior frontal gyrus and right middle frontal gyrus, as well as higher ALFF in left cerebellar anterior lobe. Using these abnormal brain areas as seeds, we observed decreased FC between left insular and left precuneus in AUVP patients. Furthermore, AUVP patients showed increased FC between left insular and left supplementary motor area. Results of correlation analysis indicated that ALFF value (z-value) in left insular was negatively correlated with the canal paresis value (p = 0.005, r = −0.483), and the FC (z-value) between left insular and left precuneus was negatively correlated with dizziness handicap inventory score (p = 0.012, r = −0.438) in patients with AUVP.ConclusionPatients with AUVP during acute period showed altered functional activity and connectivity in brain regions mainly involved in motor control and vestibular information processing. These changes in brain functional activity and connectivity were potentially attributed to decreased vestibular input resulting from unilateral peripheral vestibular impairment.